The role of cardiac T2* magnetic resonance imaging in the assessment of myocardial iron concentration in patients with beta-thalassemia major - Tushar M Kalekar,; Viraj P Shah,; Sameeh Uz Zaman,; Saad Muhammad Jaweed Shaikh,; Rachit Khandelwal, (Asian Journal of Medical Sciences, 2022)
Background: Beta-thalassemia is a group of inherited blood disorders that are characterized by reduced levels of functional hemoglobin. These patients require lifelong blood transfusions, leading to iron deposition in various tissues. Prompt detection of myocardial iron helps to assess the extent of myocardial damage and its complications. Aims and Objectives: Our study aims to establish the role of T2* cardiac magnetic resonance imaging (MRI) and its comparison with serum ferritin levels in detecting iron overload in beta-thalassemia major (TM) patients. Materials and Methods: This prospective study included 30 pediatric patients admitted to our institute with beta-TM. The patients underwent T2* cardiac MRI examinations, myocardial iron quantification was assessed, and patients were divided into groups based on the severity of iron overload. Results: In this study, there were 18 males and 12 females. Out of the total studied cases, 15 (50%) showed no evidence of iron overload, 8 (26.67%) showed mild, 4 (13.33%) showed moderate, and 3 (10%) showed severe cardiac siderosis, based on the cardiac T2* values obtained. Conclusion: T2* cardiac MRI is an accurate and invaluable tool that helps to detect iron overload in beta-TM.